Determination the best concentration of antimicrobial ingredients with a mixture of paper to create active paper packaging. Issue 1 (October 2020) - Yolanda, D S; Dirpan, A; Rahman, A N F; Kamaruddin, I; Ainani, A F
Abstract: Perishable food really needs proper handling. Therefore, various industries and researchers continue to innovate, especially in the development of packaging. The development of active packaging is a new innovation in the field of packaging technology. This packaging innovation was designed to maintain the quality of packaged food. This study aimed to obtain the best concentration of antimicrobial garlic ingredients with a mixture of paper as an active packaging material. The concentration of garlic extract used in this study was 0%, 5%, 10%, and 15%. Based on the result obtained, it could be concluded that the active paper with the addition of garlic extract concentration of 15% had the best effectiveness then followed by concentrations of 10%, 5%, and 0%. The effectiveness could be seen from the diameter of inhibition zone formation resulted.